Gouvernance locale et développement: de la contribution des CLD au renforcement de la gouvernance locale à Kisangani (RDC) - Kasongo, William-j (IJRDO - Journal of Social Science and Humanities Research, 2018)
In Kisangani, have been planed, since more of nine years, the organizations that assure a sort of local governance having for objective, the local development of the townships. It is about the Local Committees of development (CLD). This article interrogates the efficiency of the local governance through the actions of the Local Committees of Development in Kisangani and devotes on the modes of cooperation between local actors that tries to favor these organizations and, on their relation with the public powers. It also deal with the impact of these organizations on the involvement of the population to the management of the township.